1995
DOI: 10.1182/blood.v85.10.2711.bloodjournal85102711
|View full text |Cite
|
Sign up to set email alerts
|

The cloning and characterization of the human transcobalamin II gene

Abstract: Transcobalamin II (TCII) is a plasma protein that binds vitamin B12 (cobalamin; Cbl) and facilitates the cellular uptake of the vitamin by receptor-mediated endocytosis. In genetic disorders that are characterized by congenital deficiency of TCII, intracellular Cbl deficiency occurs, resulting in an early onset of megaloblastic anemia that is sometimes accompanied by a neurologic disorder. To define the genetic basis for TCII deficiency, we have cloned and characterized the human gene that encodes this protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…transcobalamin I also known as haptocorrin (TCN1) and with intrinsic factor (IF). Regec et al [29] in a comparative analysis of the placement of introns in the coding regions of human TCN2, TCN1 and IF genes, found substantial homology of the amino acids flanking these insertions and together with previous studies this supports the notion that these genes are derived by duplication of an ancestral gene. The authors suggest that despite this homology, a number of important differences in the TCN2 and TCN1 genes indicated that a major event(s) occurred during this evolutional process that randomly translocated the TCN2 gene to chromosome 22 from chromosome 11, where the human TCN1 and IF genes are located.…”
Section: Transcobalamin IIsupporting
confidence: 54%
“…transcobalamin I also known as haptocorrin (TCN1) and with intrinsic factor (IF). Regec et al [29] in a comparative analysis of the placement of introns in the coding regions of human TCN2, TCN1 and IF genes, found substantial homology of the amino acids flanking these insertions and together with previous studies this supports the notion that these genes are derived by duplication of an ancestral gene. The authors suggest that despite this homology, a number of important differences in the TCN2 and TCN1 genes indicated that a major event(s) occurred during this evolutional process that randomly translocated the TCN2 gene to chromosome 22 from chromosome 11, where the human TCN1 and IF genes are located.…”
Section: Transcobalamin IIsupporting
confidence: 54%
“…The Lazarus‐like improvement in our patient following the administration of steroids, in the context of her previous B12 loading, may have been due to an effect on blocking antibodies. It may be that the intrinsic factor antibodies in our patient were of particularly high affinity and cross‐reacted with TCII (both these proteins share significant amino acid sequence homology (13)), preventing transport of circulating B12 into cells. The administration of steroids might have abrogated this effect, allowing correction of the intracellular metabolic defect.…”
Section: Discussionmentioning
confidence: 95%
“…The MYC gene family encodes a group of transcription factors that control cell proliferation and differentiation. 4,5 Identification of at least one binding site for the MYC protein, a product of the MYC gene, on the human transcobalamin II gene, 8 showed a possible role of these two gene products in patients with abnormal transcobalamin II concentration and various malignant disorders. [9][10][11] Nevertheless, the data presented here suggest that cobalamin deficiency in Shar Peis is not related to any mutations of the MYC_CANFA gene.…”
Section: Resultsmentioning
confidence: 99%
“…MYC gene. 8 This may explain why human patients with abnormal transcobalamin II concentration had a variety of different malignant disorders, but especially multiple myeloma and lymphoproliferative disease. [9][10][11] In this context, human studies have shown that patients with transcobalamin II deficiency have a normal total circulating serum cobalamin concentration.…”
mentioning
confidence: 99%